THEACHER STRATEGIES FOR ENHANCHING STUDENT LEARNING MOTIVATION IN EARLY GRADE MATHEMATICS AT SD ISLAM SABILILLAH CUKIR. - Eka Putri, Aulia; zahrani susilo , claudya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to investigate and describe the pedagogical strategies employed by teachers to enhance students' learning motivation in mathematics within the lower-grade classes of SD Islam Sabilillah Cukir. The primary problem addressed in this research is the common perception among early-grade students that mathematics is a difficult and intimidating subject, which often leads to low engagement, anxiety, and a lack of interest in numerical concepts. To address this issue, a qualitative research methodology with a case study approach was utilized. Data were collected through structured observations, semi-structured interviews with classroom teachers, and extensive documentation of learning activities. The results of the research indicate that teachers implement a multifaceted strategy involving the use of concrete manipulative media, the integration of Islamic values into mathematical contexts, and a consistent reward-and-praise system to build students' confidence. Furthermore, the findings reveal that creating a joyful learning atmosphere through